168k views
2 votes
Factor the expression below. x 2 − 12 ⁢ x + 36 A. (x + 6)(x + 6) B. (x − 6)(x + 6) C. 6(x2 − x + 6) D. (x − 6)(x − 6)

2 Answers

6 votes

Answer:

D) = (x - 6 )(x - 6)

Explanation:

x^2 - 12x + 36

= x^2 -6x -6x + 36

= x(x - 6) -6(x - 6)

= (x - 6 )(x - 6)

User Glm
by
5.7k points
2 votes

Answer:


\boxed{\tt (x-6)(x-6)}

Explanation:

To factor x²−12x+36 we need to find two numbers that add together to get -12 and multiply together to get 36:-

Let's try -6 and -6:-


\tt -6+-6 = -12


\tt -6* -6 = 36


\tt (x-6)(x-6)

_________________

Hope this helps!

Have a nice day!

User Berndbausch
by
4.7k points